Endothelial cell phagocytosis of senescent neutrophils decreases procoagulant activity - Gao, Chunyan; Xie, Rui; Li, Wen; Zhou, Jin; Liu, Shuchuan; Cao, Fenglin; Liu, Yue; Ma, Ruishuang; Si, Yu; Liu, Yan; Bi, Yayan; Gilbert, Gary E.; Shi, Jialan (Thrombosis and Haemostasis, 2013)
Abundant senescent neutrophils traverse the vascular compartment and may contribute to pathologic conditions. For example, they become procoagulant when undergoing apoptosis and may contribute to thrombosis or inflammation. Our previous studies demonstrated a dominant clearance pathway in which the neutrophils can be phagocytosed by liver macrophages. The aim of this study was to explore an alternate pathway of neutrophil clearance by endothelial cells. Phagocytosis of the neutrophils by endothelial cells was performed using various experimental approaches including flow cytometry, confocal microscopy and electron microscopy assays in vitro and in vivo. Procoagulant activity of cultured neutrophils was evaluated by coagulation time, factor Xase and prothrombinase assays. Lactadherin functioned as a novel probe for the detection of phosphatidylserine on apoptotic cells, an opsonin (bridge) between apoptotic cell and phagocyte for promoting phagocytosis, and an efficient anticoagulant for inhibition of factor Xase and thrombin formation. When cultured, purified human neutrophils spontaneously entered apoptosis and developed procoagulant activity that was directly related to the degree of phosphatidylserine exposure. Co-culture of aged neutrophils and endothelial cells resulted in phagocytosis of the neutrophils and prolonged coagulation time. Lactadherin diminished the procoagulant activity and increased the rate of neutrophil clearance. In vivo, neutrophils were sequestered by endothelial cells after blockade of Kupffer cells, a process that was dependent upon both phosphatidylserine exposure and P-selectin expression. Thus, the ability of endothelial cells to clear senescent neutrophils may limit the procoagulant and/or inflammatory impact of these cells.
Keywords: Phagocytosis; endothelial cell; neutrophil; procoagulant activity; lactadherin